2019
DOI: 10.9770/jssi.2019.9.1(8)
|View full text |Cite
|
Sign up to set email alerts
|

Security of Organizational Changes via Operational Integration: Ensuring Methodology

Abstract: The concept and the need of organizational changes in the corporate environment in order to ensure a lasting effect of economic and strategic security were determined. The methodology for conducting organizational changes based on the use of optimal operational integration, which forms a decomposition of the company's development goals and forms the field of economic security was proposed. The model analysis of ensuring effective organizational security and operational integration of the functional units of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Interestingly, in recent work by Hilorme et al (2019a) on the introduction of energy-saving technologies into enterprise, results demonstrated that the lack of cooperation and coordination of activities, and the low level of interaction in companies led to a decrease in the quality of the information signal in communication channels, as support for decision making. In research carried out by Drobyazko et al (2019b) on the security of organizational changes via operational integration, it was proved that the methodological approaches to changes in the work of companies should be based on the principles of consistency, complexity and functionality. The authors here discuss the implementation of such principles through the following types of change: (1) unplanned change (a reaction of the enterprise to any events and trends that may be threatening or, conversely, provide unexpected new opportunities); (2) planned change (willingness to react at the right time for favorable opportunities or problems in accordance with the goal of the most complete use or maximum leveling of the impact); (3) imposed change (changes that occur under the influence and on the initiative of the management of the enterprise in order to adequately respond to urgent situations or events); and (4) integration change (increasing the "internal" and reducing the "external" integration activities, which will lead to an increase in the level of functional interaction).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in recent work by Hilorme et al (2019a) on the introduction of energy-saving technologies into enterprise, results demonstrated that the lack of cooperation and coordination of activities, and the low level of interaction in companies led to a decrease in the quality of the information signal in communication channels, as support for decision making. In research carried out by Drobyazko et al (2019b) on the security of organizational changes via operational integration, it was proved that the methodological approaches to changes in the work of companies should be based on the principles of consistency, complexity and functionality. The authors here discuss the implementation of such principles through the following types of change: (1) unplanned change (a reaction of the enterprise to any events and trends that may be threatening or, conversely, provide unexpected new opportunities); (2) planned change (willingness to react at the right time for favorable opportunities or problems in accordance with the goal of the most complete use or maximum leveling of the impact); (3) imposed change (changes that occur under the influence and on the initiative of the management of the enterprise in order to adequately respond to urgent situations or events); and (4) integration change (increasing the "internal" and reducing the "external" integration activities, which will lead to an increase in the level of functional interaction).…”
Section: Resultsmentioning
confidence: 99%
“…In line with this, the first five themes extracted through content analysis (response, resource, structure, network, data output) are able to function as they support the already existing operational environments with the scope to fill the gaps when a crisis hits, as a community is held together through the bonding agents that are pre-existent to any structure. Additionally the new emergent areas from case studies in response to suddenly experienced crisis (second part of the research), focus on operational recovery (process improvement, training, policy feedback) and can be aligned to what is termed as 'business reduction (recovery strategy)' in the typology of basic strategies, directions and types of changes is proposed in accordance with business development strategies (Drobyazko et al 2019b).…”
Section: Basis For Tool Developmentmentioning
confidence: 99%
“…The problems of development of informatization of education are revealed in the works of (Jackson & Tomlinson, 2009;Reidenberg et al, 2013;Drobyazko et al, 2019). A number of scientific papers reflect the main approaches to the design of entrepreneurship education (Caves, 2000;Parkman et al, 2012;Drobyazko et al, 2019a). The use of modern educational technologies is actively studied by (Anjali & Pandey, 2013;Utomo et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2018)). It should be noted that development does not always contribute to the progress and structural changes (Voegtlin, C., & Scherer, A. G. (2017) processes can become the results of developmentregression, in other words such development that has destructive nature (Drobyazko, S., et al (2019)).…”
Section: Literature Surveymentioning
confidence: 99%